Antioxidant and Anti-Breast Cancer Potentials of the Hydrophilic Fraction from Soft Coral Nepthea sp.: In Vitro and In Silico Assessment - Sahidin Sahidin; Baru Sadarun; Marianti A Manggau; Adryan Fristiohady; Dzaky Aulia Rahman; Agung Wibawa Mahatva Yodha; Arfan Arfan; Andini Sundowo; Sofa Fajriah (Universitas Jenderal Soedirman, 2026)
ABSTRACT. Soft corals of the genus Nepthea are recognized as rich sources of marine bioactive compounds, yet their hydrophilic metabolites remain poorly explored. This study characterized the hydrophilic fraction of Nepthea sp. and assessed its antioxidant and anti–breast cancer activities through in vitro and in silico approaches. Ethyl acetate extract (EAE) of Nepthea sp. was fractionated into six subfractions (F1–F6), with F5–F6 representing hydrophilic fractions. Phytochemical screening, TPC, TFC, and LC–MS/MS analyses were conducted alongside antioxidant (DPPH, ABTS), cytotoxicity (MTT, MCF-7), and molecular docking assays against xanthine oxidase (XO) and estrogen receptor alpha (ERα). Phytochemical profiling revealed alkaloids, phenolics, flavonoids, saponins, and terpenoids, with F5 exhibiting the highest TPC (73.11 mg GAE/g) and TFC (2.20 mg QE/g). LC–MS/MS identified rengyolester and piperolactam-C9:1(8E) in F5 and isosalsoline and 3-tert-butyl-4-methoxyphenol in F6. F5 demonstrated stronger antioxidant (DPPH IC₅₀ = 67.39 mg/L; ABTS IC₅₀ = 54.12 mg/L) and cytotoxic (MTT IC₅₀ = 42.68 mg/L) activities than F6. Docking analysis supported these results: rengyolester and piperolactam-C9:1(8E) showed strong affinities toward XO (−8.4, −8.7 kcal/mol) and ERα (−7.6, −7.4 kcal/mol), forming interactions with key residues (Phe914, Phe1009, Glu353, Leu525) similar to reference ligands. The hydrophilic fraction particularly F5 contains multifunctional metabolites exhibiting both antioxidant and anticancer properties. The synergistic role of phenolic and terpenoid constituents highlights Nepthea sp. as a promising marine source of bioactive therapeutic leads. Keywords: Antioxidant, breast cancer, hydrophilic fraction, molecular docking, Nepthea sp.